The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/0016986209352682
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between the Overexcitabilities and Self-Concepts of Gifted Adolescents via Multivariate Cluster Analysis

Abstract: The purpose of this study was to explore the relationship between gifted adolescents’ forms of overexcitabilities and self-concepts. Clusters of adolescents were formed on the basis of their overexcitabilities, and these clusters of adolescents were then compared with regard to their self-concept scores. Gender differences were also examined. The sample consisted of 379 gifted adolescents, ranging in age from 11 to 16 years of age. Forms of overexcitabilities were measured using the Overexcitabilities Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 46 publications
2
16
0
6
Order By: Relevance
“…Following the DHC, the ALCESTE software divides the corpus into several classes that group together individuals according to the similarity of their profiles as compared to the complete set of indicators used. As a cluster analysis procedure, the goal is to form groups that maximize both intragroup similarities and intergroup dissimilarities (Rinn, Mendaglio, Rudasill, & McQueen, 2010). In a second step, the software makes it possible to show the correlation that exists between profiles and illustrative variables (e.g., sociobiographical elements) defined by the researcher.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Following the DHC, the ALCESTE software divides the corpus into several classes that group together individuals according to the similarity of their profiles as compared to the complete set of indicators used. As a cluster analysis procedure, the goal is to form groups that maximize both intragroup similarities and intergroup dissimilarities (Rinn, Mendaglio, Rudasill, & McQueen, 2010). In a second step, the software makes it possible to show the correlation that exists between profiles and illustrative variables (e.g., sociobiographical elements) defined by the researcher.…”
Section: Methods Of Analysismentioning
confidence: 99%
“…For example, females score higher than males on Sensual and Emotional OEs (Ackerman, 1997;Bouchet & Falk, 2001;Gross, Rinn, & Jamieson, 2007;Miller et al, 1994;Tieso, 2007), whereas they score lower on Psychomotor and Intellectual OEs (Bouchet & Falk, 2001;Lysy & Piechowski, 1983;Miller et al, 1994;Rinn, Mendaglio, Moritz Rudasill, & McQueen, 2010;Tieso, 2007). The relationship between gender and Imaginational OE is less consistent; depending on the study, females have sometimes been found to score higher than males (Ackerman, 1997;Gross et al, 2007) and sometimes lower (Bouchet & Falk, 2001).…”
Section: Gender Differencesmentioning
confidence: 98%
“…DuBois and Hirsch (2000) argue that by affording higher priority to linking the study of self‐esteem to other aspects of the development, researchers would be better positioned to understanding self‐processes in adolescence. Recent findings focus on the relationships between perceptions of the self and a range of variables: diet and appearance satisfaction (Barker & Bornstein, 2010), neural activity (Pfiefer et al., 2009), self‐deception and self‐liking (Mar, DeYoung, Higgins, & Peterson, 2006), overexcitability (Rinn, Mendaglio, Rudasill, & McQueen, 2010), body weight and obesity (McCullough, Muldoon, & Dempster, 2009; O'Dea, 2006), emotional expression (Polce‐Lynch, Myers, Kliewer, & Kilmartin, 2001), and smoking behaviour (Glendinning & Inglis, 1999).…”
Section: Introductionmentioning
confidence: 99%